The temporal distribution and occurrence of impacts and movement relative to peak periods in men's rugby union - Peek, R. J.; Fleming, J. A.; Carey, D. L.; Middleton, K. J.; Gastin, P. B.; Clarke, A. C. (Journal of Science and Medicine in Sport, 2022)
Objectives: This study identifies the distribution (as a percentage of the positional peak) and occurrence (within a half) of 1-min movement characteristics (m·min-1) and contact-based events (impact·min-1) during professional rugby union game play. Design: Within 95 rugby union games, players wore global positioning system (GPS) devices (n=1422 player-game files, 160 athletes). One-minute rolling-window averages were calculated with the maximum and mean value being recorded for each dependent variable; relative distance (m·min-1) and impacts (impact·min-1), then standardised by the positional peak mean. Methods: The distribution of these variables accumulated in 10% increments of the peak were determined as was their occurrence throughout a playing half for each positional group. Results: The greatest distribution of game play (%) was observed at ~30-39% of the positional peak for movement and with no impacts. The greatest occurrence of maximum positional peak 1-min movement periods occurred at the beginning of each half and declined as the half went on. Peak impact characteristics, however, were found to be more sporadic across a half. Conclusions: These findings suggest that the distribution of positional peak 1-min movement (80-100%+) and peak impacts (4+) were <5% of overall game play, and observed <2% of total occurrences. This highlights that practitioners should alter training drills by time, volume, and intensity in order to replicate the peak intensities of game play.